2005
DOI: 10.1097/01.jsm.0000158255.78040.ec
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Exercises on 13C-Nandrolone Excretion in Trained Athletes

Abstract: The results of this study suggest that physical exercise cannot be considered as a reliable parameter that systematically affects nandrolone metabolite concentrations in the urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Contaminated supplements and endogenous production as revealed in a 13C nandrolone excretion study in trained athletes4 may, in part at least, have impacted on these positive cases. Further support for this idea emerged from a study that found traces of the metabolites of nandrolone following 90 min of football in healthy volunteers 5. This finding led to a 2 ng per mL cut-off level for nandrolone metabolites being introduced as an adverse analytical finding.…”
Section: A Historical Perspectivementioning
confidence: 99%
“…Contaminated supplements and endogenous production as revealed in a 13C nandrolone excretion study in trained athletes4 may, in part at least, have impacted on these positive cases. Further support for this idea emerged from a study that found traces of the metabolites of nandrolone following 90 min of football in healthy volunteers 5. This finding led to a 2 ng per mL cut-off level for nandrolone metabolites being introduced as an adverse analytical finding.…”
Section: A Historical Perspectivementioning
confidence: 99%
“…36 The analysis of urinary metabolites by gas chromatography/combustion/isotope ratio mass spectrometry (GC/C/ IRMS) has been shown to be useful in determining their origin, endogenous or exogenous. [37][38][39][40] It is routinely used for confirmation in a few laboratories; major improvements were needed with regard to sample purification and instrumental conditions to reach the level of sensitivity required for the analysis of low levels of 19-norsteroid urinary metabolites.…”
Section: Norsteroids: Metabolism Excretion and Detection In Human Umentioning
confidence: 99%
“…Nandrolone is one of the most abused anabolic steroid in sports and the presence of its metabolites in urine at low concentrations is always subject to discussion, because of a possible endogenous production or intake of contaminated nutritional supplements [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%